Pengaruh Manajemen Aset, Likuiditas, dan Struktur Modal Terhadap Kinerja Keuangan - Ratri Nur Indah Sari; Nawang Kalbuana; Deden Subagja (UNIVERSITAS MARITIM AMNI SEMARANG, 2025)
Financial performance describes the financial position of a company that is analyzed to provide an overview of the company's performance during a certain period. Several factors that influence financial performance include asset management, liquidity, and capital structure. This study aims to identify the effect of asset management (TATO), liquidity (CR), and capital structure (DER) on financial performance (ROA) in food and beverage companies for the period 2019-2023, both individually and together. This type of research is quantitative research using secondary data through access to the Indonesia Stock Exchange website or the official website of the related company. Sample selection using the Purposive Sampling technique, resulting in 14 companies from a total population of 42 companies. The analysis techniques used include descriptive statistical analysis, classical assumption tests, multiple linear regression analysis, hypothesis testing (t-test and F-test), and coefficient of determination. The data processing process uses SPSS version 23. The results of the t-test (partial) show that the asset management and liquidity variables have no effect on financial performance. Meanwhile, the capital structure variable shows a negative and significant effect on financial performance. The results of the F test (simultaneous) indicate that asset management, liquidity, and capital structure together have a significant effect on financial performance. The Adjusted R Square value of 0.406 indicates that 40.6% of the variation in financial performance is explained by the three variables, while the remaining 59.4% is influenced by other variables outside this research model.